PENGARUH PEMBERIAN DOSIS PROBIOTIK YANG BERBEDA TERHADAP PERTUMBUHAN DAN MORTALITAS UDANG VANAMEI (Litopenaeus vanammei) - muzaqqi, iqbal; nuhman; trisyani, ninis (FISHERIES Jurnal Perikanan dan Ilmu Kelautan, 2022)
Vannamei shrimp productivity is influenced by the carrying capacity of the pond and the environment, good fry quality and water quality. Microorganisms in probiotics are very beneficial for living things. The addition of probiotics in artificial vaname shrimp feed can increase the nutritional content of protein feed and maintain the balance of digestive tract microbes. The research design used was a completely randomized design with 4 treatments and 6 times. The best treatment results were the probiotic dose of 20 ml/kg with a growth rate of 6%, absolute weight growth of 2.30 grams and mortality of 8.59%